A prospective study antenatally detected hydronephrosis and their postnatal evaluation and management - Vinayagam, Karpaga; Saravanan, C. (International Surgery Journal, 2020)
Background: Detection of urologic anomalies prenatally permits fetal interventions that avoid complications in rare cases of bladder outlet obstruction with oligohydramnios even though their final benefits still remain controversial. To analyse the incidence of ureteropelvic junction (UPJ) obstruction in antenatally detected hydronephrosis cases. Methods: This prospective study was conducted February 2019 to August 2019 at the Institute of Child Health and Hospital for Children Egmore, Chennai. All the cases of hydronephrosis which were detected antenatally and those children presented with hydronephrosis in the neonatal period were taken for this study. Totally 58 cases were analyzed in the study, among that 32 cases detected antenatally with UPJ obstruction. Their epidemiology and their immediate postnatal findings (USG abdomen by 3-7 days, IVP and DTPA by 4-6 weeks) were recorded and the percentage of cases in which pelvic-ureteric junction obstruction was significant. Results: Among the cases that were diagnosed to have hydronephrosis antenatally (46), 69% (32/46) had UPJ obstruction, 21% (10/46) had bilateral hydronephrosis, 6.5% (3/46) had vesicoureteric reflux and rest had other anomalies (1/46). Conclusions: Antenatal hydronephrosis (ANH), one of the most common abnormal findings on the antenatal ultrasound (US), continues to increase as the standard of care includes the 2nd trimester US. US is the mainstay of the postnatal evaluation and voiding cystourethrogram may be safely reserved for high-grade ANH or dilated distal ureter. New urinary biomarkers may offer promising potential for more accurate risk stratification in the near future.